Optimization of Catfish Pond Water pH with PID Control using Outseal PLC - Abdillah Ali Rachman; Muhamad Ariandi (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
The increasing need for national consumption fish every year makes the business of cultivating consumption fish such as catfish increasingly developed. In catfish farming, the pH level factor in water affects the growth and development of catfish. If the pH level is not appropriate, it causes catfish disease and catfish appetite decreases. So it is necessary to control the pH level of water automatically which makes it easy to maintain pH levels in fish ponds using PID control. The system is designed using Outseal which is an Arduino bootloader-based PLC (Progammable Logic Control) which is open source at an affordable price connected to the RDD-AFE-001 sensor to send readings of actual pH levels into the PID control process. The PID output is in the form of a pwm value to run the L2890N motor driver as a nutrient pump speed regulator based on the pH value. The results of analyzing the value of PID parameters using simulink software obtained the value of Kp = 30, Ki = 20 and Kd = 15. The Propotional role produces a better rise time so that the pH sensor reading response is faster, then the integral role eliminates overshoot which causes more accurate sensor readings and the derivative role eliminates steady state errors that affect the stability of the pH sensor reading. The test results successfully maintain the pH level in water with a value of 7.0 with water temperatures ranging from 26 ° C - 30 ° C. The existence of this system can increase the growth and stability of the pH sensor reading. With this system can improve the growth and development of catfish and away from contracting diseases and facilitate farmers in terms of maintaining the pH level of catfish water.